Safety of oral non-selective non-steroidal anti-inflammatory drugs in osteoarthritis: What does the literature say? - Cooper, C; Chapurlat, R; Al-Daghri, N; Herrero-Beaumont, G; Bruyère, O; Rannou, F; Roth, R; Uebelhart, D; Reginster, J (Springer International Publishing, 2019)
Non-steroidal anti-inflammatory drugs (NSAIDs) are widely recommended and prescribed to treat pain in osteoarthritis. While measured to have a moderate effect on pain in osteoarthritis, NSAIDs have been associated with wide-ranging adverse events affecting the gastrointestinal, cardiovascular, and renal systems. Gastrointestinal toxicity is found with all NSAIDs, which may be of particular concern when treating older patients with osteoarthritis, and gastric adverse events may be reduced by taking a concomitant gastroprotective agent, although intestinal adverse events are not ameliorated. Cardiovascular toxicity is associated with all NSAIDs to some extent and the degree of risk appears to be pharmacotherapy specific. An increased risk of acute myocardial infarction and heart failure is observed with all NSAIDs, while an elevated risk of hemorrhagic stroke appears to be restricted to the use of diclofenac and meloxicam. All NSAIDs have the potential to induce acute kidney injury, and patients with osteoarthritis with co-morbid conditions including hypertension, heart failure, and diabetes mellitus are at increased risk. Osteoarthritis is associated with excess mortality, which may be explained by reduced levels of physical activity owing to lower limb pain, presence of comorbid conditions, and the adverse effects of anti-osteoarthritis medications especially NSAIDs. This narrative review of recent literature identifies data on the safety of non-selective NSAIDs to better understand the risk:benefit of using NSAIDs to manage pain in osteoarthritis.